LA PENA ALTERNATIVA EN LA LEY DE JUSTICIA Y PAZ (2016)
This reflection article analyzes the remuneration of punishment in Law 975 of 2005 in order to establish if the system satisfies the parameters defined by the international criminal law for prosecution of the most serious crimes of concern to the international community as a whole.